Role Stressors, Spiritual Intelligence, and Auditor Performance: Faktor Stres Peran, Kecerdasan Spiritual, dan Kinerja Auditor - Ramadhani, Nurma Ayu; Biduri , Sarwendah (Indonesian Journal of Law and Economics Review, 2025)
Background: Auditor performance is crucial for audit quality and public trust, yet role stressors often impair performance. Specific background: Previous studies reported mixed results regarding role conflict, ambiguity, overload, and leadership styles. Knowledge gap: Limited evidence on how spiritual intelligence moderates these relationships in Indonesian audit firms. Aims: This study examines the relationships between role conflict, role ambiguity, role overload, leadership styles, and auditor performance, with spiritual intelligence as a moderator. Results: Based on questionnaire data from 50 auditors and PLS analysis, role ambiguity and role overload significantly relate to auditor performance, while role conflict and leadership styles do not. Spiritual intelligence positively moderates the relationships for role conflict and leadership styles but not for role ambiguity or overload. Novelty: The paper highlights differential moderating effects of spiritual intelligence across distinct role stressors. Implications: Findings suggest targeted human-resources interventions that cultivate spiritual competencies may buffer specific workplace stressors to preserve auditor performance. Highlights: Spiritual intelligence moderates conflict-perf and leadership-perf links. Role ambiguity and overload directly associate with auditor performance. Sample from KAP in Surabaya and Sidoarjo PLS analysis used. Keywords: Role Conflict, Role Ambiguity, Role Overload, Spiritual Intelligence, Auditor Performance